FAKTOR-FAKTOR PENENTU KUALITAS AUDIT DAN KEPUASAN AUDITEE PERSEPSIAN DI PEMERINTAHAN DAERAH - Ni Kadek Sriwati (Ekomen, 2014)
This research aims to analyze the determinants of perceived audit quality and auditee satisfaction factors in local government. This study adopted research by Samelson (2006) with some modification. The object of the research was institute/SKPD the local government area of the province of Yogyakarta (DIY) that bound in implementation finances management provinces (finances management provinces authority) and responsibility toward utilizing provinces budget.This study used purposive sampling technique in the data collection. The data was obtained by disseminate questionnaire in the government city of Yogyakarta, Sleman, Bantul, Kulon Progo Regency, and Gunung Kidul. The data analysis was conducted Ordinal Logistic Regression with SPSS 15.0.The result of this study demonstrated that 6 audit quality attributes variable (Industry expertise, Responsiveness, Professional care, Commitment, Conduct of audit field work, and Member characteristics) had significantly positive correlation on perceived audit quality. This study also found that 7 audit quality attributes variable (Experience, Industry expertise, Compliance, Professional care, Commitment, Conduct of audit field work, and Member characteristics) had significantly positive correlation on perceived auditee satisfaction. Futhermore, it ignored another attributes of audit quality to determinants of perceived audit quality and auditee satisfaction factors to local government.Key words : Perceived Audit Quality, Auditee Satisfaction, Attributes of audit quality and Ordinal Logistic Regression (OLR).